2019
DOI: 10.1186/s12867-019-0124-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic responses to grazing reveal the metabolic pathway leading to the biosynthesis of domoic acid and highlight different defense strategies in diatoms

Abstract: Background A major cause of phytoplankton mortality is predation by zooplankton. Strategies to avoid grazers have probably played a major role in the evolution of phytoplankton and impacted bloom dynamics and trophic energy transport. Certain species of the genus Pseudo-nitzschia produce the neurotoxin, domoic acid (DA), as a response to the presence of copepod grazers, suggesting that DA is a defense compound. The biosynthesis of DA comprises fusion of two precursors, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…Previous studies have demonstrated limited trace metal chelation by DA, affording a potential selective advantage for diatoms thriving in iron-limited coastal regimes ( 58 , 59 ). Other work has suggested a role for DA in grazer defense, particularly with respect to copepod grazing in the diatom system ( 60 ). However, no studies to date have provided a concrete ecological mechanism beyond reasonable doubt in both diatoms and red algae.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated limited trace metal chelation by DA, affording a potential selective advantage for diatoms thriving in iron-limited coastal regimes ( 58 , 59 ). Other work has suggested a role for DA in grazer defense, particularly with respect to copepod grazing in the diatom system ( 60 ). However, no studies to date have provided a concrete ecological mechanism beyond reasonable doubt in both diatoms and red algae.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Horizontal gene transfer in protists is perhaps a neglected phenomenon and may be exacerbated by widespread viral infections [47]. For this hypothesis to be examined, a clear evolutionary role of DA should be established, which is at the moment not the case since proposed roles range from grazer deterrence [10,11,48] to metal chelation [4][5][6], while strains and species are all known to fare well in the absence of DA production. On the other hand, the competitive advantage of DA production may be clearer when local environmental conditions are considered.…”
Section: Phylogenetic Relationships Between Toxic and Non-toxic Strainsmentioning
confidence: 99%
“…At the moment, however, the design of suitable probes is hampered by the lack of sequences from different species and could perhaps only be developed for P. multiseries and now with our data for P. multistriata. We acknowledge that there are other genes involved in the biosynthesis of DA [9,11] that we did not examine in this work and that may prove to be more conserved and thus better targets for such efforts. However, the focus of this work was on the toxicity profiles of NE Adriatic strains, and we hope that this work will open new opportunities for the study of gene expression and the discovery of genes involved in the synthesis of DA.…”
Section: Daba In Selected Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The toxin is a simple neurotoxic amino acid called domoic acid (DA). The chemical compounds, metabolic precursors, and the penultimate enzymatic steps for the biosynthesis of DA were recently described (Maeno et al, 2018;Brunson et al, 2018;Harðardóttir et al, 2019) but the final isomerization reaction, sources, and compartmentalization are yet to be elucidated.…”
Section: Pseudo-nitzschia Toxicity -Impact and Inductionmentioning
confidence: 99%